2017
DOI: 10.1039/c7dt02230a
|View full text |Cite
|
Sign up to set email alerts
|

A coordination polymer based on dinuclear (pyrazinyl tetrazolate) copper(ii) cations and Wells–Dawson anions for high-performance supercapacitor electrodes

Abstract: A new coordination polymer, (Hbpe)(Hbpe){[Cu(pzta)(HO)][PWO]}·5HO (1) (pztaH = 5-(2-pyrazinyl) tetrazolate, bpe = bis(4-pyridyl)ethylene), was synthesized by the hydrothermal method. The structure was determined by single crystal X-ray diffraction analyses and further characterized by the SEM, EDS, BVS, FTIR, and PXRD techniques. In 1, the [PWO] (PW) clusters as bidentate connectors link [Cu(pzta)(HO)] dinuclear copper(ii) complexes to form inorganic-organic chains. These chains and the [Hbpe] counter-cations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…(c) Relationship between crystal structure on the molecular level and their capacitance performance of the POM hybrids : POM is a class of nano‐scaled molecules with poor conductivity due to their isolated cluster structures. Herein, combining POM with metal cations or metal‐organic segments is an effective way to improve their capacitor performance,, yet the mechanism has been not clear. In order to initially explore that mechanism, two systems of POM hybrids have been prepared (Scheme ) and the capacitor performance have been compared.…”
Section: Resultsmentioning
confidence: 99%
“…(c) Relationship between crystal structure on the molecular level and their capacitance performance of the POM hybrids : POM is a class of nano‐scaled molecules with poor conductivity due to their isolated cluster structures. Herein, combining POM with metal cations or metal‐organic segments is an effective way to improve their capacitor performance,, yet the mechanism has been not clear. In order to initially explore that mechanism, two systems of POM hybrids have been prepared (Scheme ) and the capacitor performance have been compared.…”
Section: Resultsmentioning
confidence: 99%
“…In the following year, Zhang and coworkers designed a zinc‐porphyrin monomer and prepared the SC electrodes by the electropolymerization method to afford a conducting metal‐organic polymer ( IX ) 71 . The metal‐organic compounds exhibiting the SC properties were extended to those containing the Schiff‐base ligands ( XV ), 75 ferrocene‐based ligands ( XVI ) 76 and polyoxometalates (POMs, XVII ) 77 in 2017. From 2018 onwards, research interests of the metal‐organic compounds of the first transition metal series began to move to the two‐dimensional MOFs (eg, XVIII , XIX and XXI ) with planar polyamine and polyphenol ligands (Figure 9).…”
Section: Introductionmentioning
confidence: 99%
“…reported that the phosphotungstic acid PTA/Al 2 (SO 4 ) 3 ⋅ 18 H 2 O can be used as a symmetric capacitor, and showed that the capacitance is 240 F g −1 at 6 mA. In 2017, Ma et al . reported the electrochemical performance of (H 2 bpe)(Hbpe) 2 {[Cu(pzta)(H 2 O)][P 2 W 18 O 62 ]} ⋅ 5 H 2 O with 168 F g −1 and a retention of 90.7 % after 1000 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, Wang et al [27] reported that the phosphotungstic acidP TA/Al 2 (SO 4 ) 3 ·18 H 2 Oc an be used as a symmetric capacitor,a nd showed that the capacitance is 240 Fg À1 at 6mA. In 2017, Ma et al [28] reported the electrochemicalp erformance of (H 2 bpe)(Hbpe) 2 {[Cu(pzta)(H 2 O)] [P 2 W 18 O 62 ]}·5H 2 Ow ith1 68 Fg À1 and ar etention of 90.7 %a fter 1000 cycles. However,P OMs also have the problems of easy agglomeration, small specific surfacea rea, and large self-resistance.…”
Section: Introductionmentioning
confidence: 99%